Top-oil temperature model for transformers based on nonlinear thermal resistance, lumped capacitance and thermal-electrical analogy - Roslan, Muhammad Hakirin; Azis, Norhafiz; Jasni, Jasronita; Ibrahim, Z. (Universiti Putra Malaysia Press, 2017)
Top-Oil Temperature (TOT) is one of the basic components to estimate the Hot-Spot temperature (HST) of the transformers. This paper presents an alternative TOT model based on the heat transfer theory that utilises Nonlinear Thermal Resistance (NTR) and Lumped Capacitance (LC) approaches. It is applied in a thermal-electrical analogy and the heat transfer equivalent equation is determined. This model is tested on a measured TOT of 250 MVA ONAF and 400 MVA ONAF transformers obtained from IEC 60076-7 and previous research. A comparison of TOT is carried out with the existing models IEC 60076-7 exponential and IEEE Loading Guide clause 7 methods. It is found that the thermal model based on the NTR and LC approach could determine the measured TOT closer than the existing methods available in the standards.